A Pengaruh latihan drill terhadap akurasi groudstroke atlet semen padang tenis club: pengaruh latihan drill - faiz, muhammad faiz wahyudy; Muhammad Sazeli Rifki,; ahmad caeroni,; Donal Syafrianto, (Jurnal IKEOR, 2026)
Abstract: The problem in this research is the low groundstroke accuracy of Semen Padang Tennis Club athletes. The purpose of this study was to determine the effect of drill training on improving the groundstroke accuracy of Semen Padang Tennis Club athletes. This research was a quasi-experimental study. It was conducted from July to August 2025 at the Semen Padang Tennis Court in Padang City, West Sumatra. The population was all 34 athletes from the Semen Padang Tennis Club. The sampling technique used was total sampling, considering that the sample was drawn from the 12-18 age group, the most active, accomplished athletes who had participated in competitions. Therefore, the sample size was 15 athletes. The instrument used in this study was the International Tennis Number (ITN) On Court Assessment Guide. Data were analyzed using the Shapiro-Wilk normality test and a paired sample t-test. The results showed an increase in the average groundstroke accuracy score from 24.87 in the pretest to 29.53 in the posttest. The paired sample t-test yielded a significance value of 0.030 (p <0.05), indicating a significant effect of drill training on improving athletes' groundstroke accuracy.